Immune status and cytokine spectrum as predictors of the risk of severe disease and performance indicators of intensive therapy in patients with coronavirus infection COVID-19 - V.F. Sadykov; R.A. Poltavtseva; A.V. Chaplygina; N.V. Bobkova (Analiz Riska Zdorovʹû, 2022)
The pandemic caused by a new strain of the SARS-CoV-2 coronavirus has swept the whole world but effective methods for treating this severe pathology have not yet been created. It has now been established that a risk of a severe course of COVID-19 is not so much a patient's age itself, but so-called age-related diseases; the renin-angiotensin system (RAS) is directly or indirectly involved into their development. The SARS-CoV-19 virus interacts with one of the main regulatory elements of this system, ACE2, and disrupts the balance between the two RAS branches. This ultimately manifests itself in an increase in levels of angiotensin II, which, through binding to the angiotensin type 1 receptor (AT1R), causes a number of pathological conditions, including hypertension, atherosclerosis, and cardiovascular diseases, enhances cell proliferation, apoptosis, death of vascular endothelial cells, etc. This process has been described in many reviews by Russian and foreign authors. However, cells of innate and adaptive immunity are another less well-described but no less important target of angiotensin II. The consequences of this interaction are analyzed in detail in this review. With COVID-19, dendritic cells are activated, macrophage proliferation and neutrophil infiltration increase with further involvement of CD4-lymphocytes and other cellular elements of the adaptive immunity in this process. Hyperactivation of the immune system is accompanied with the release of a large amount of pro-inflammatory cytokines, which can lead to the occurrence of a cytokine storm. The picture is aggravated by the inhibitory effect produced by the virus itself on the synthesis of signaling interferons at initial stages in its internalization into the cell. A separate section in the review ad-dresses the problem how to predict a risk of a developing serious condition and search for its predictors by analyzing the state of the RAS and ratios of key cellular elements in the immune system. This is extremely important for making decisions concerning the amount of necessary medical care and strategies for subsequent treatment.